Assessing Megastigmus specularis (Hymenoptera: Megastigmidae) infestations in a Fraser fir (Abies fraseri (Pursh) Poir.) clonal seed orchard of the southern Appalachians. Issue 8 (16th November 2020) - Matallana-Ramirez, Lilian P.; Goode, Kelly; Bertone, Matthew; Janšta, Petr; Burks, Roger; Jetton, Robert; Frampton, John
ABSTRACT: The Christmas tree industry is mainly supplied with seeds from natural stands and genetically improved germplasm from clonal seed orchards (CSOs). Chalcid wasps ( Megastigmus spp.) have a negative effect on the value of seedlots by reducing the quantity of viable seeds and represent a risk for national and international seed trade. Seed radiographies, field observations and seed-dissections from 25 Fraser fir ( Abies fraseri (Pursh) Poir.) clones were used to determine chalcid infestation in a CSO of the southern Appalachians. We provided direct evidence that Mesopolobus cf. pinus is an ectoparasitoid of M. specularis, proposed a model that linked different aspects of the biology of these species and discussed host–insect phenological relationships. Infestation of seeds in some clones across surveys, suggested a potential genetic component to chalcid wasp's prevalence. Cold and dark rearing regimens were used to identify changes in adult insect emergence after variation of overwinter conditions. Both the frequency and the time of emerging M. specularis adults from seeds were affected by the duration of the treatments but not statistical differences were found for Mesopolobus cf. pinus . We present evidence for the efficiency of a gravity-seed cleaning method eliminating upwards of 95% of chalcid-infested seeds.